2013
DOI: 10.1186/1471-2458-13-486
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and socioeconomic and geographical inequalities of household food insecurity in the Paris region, France, 2010

Abstract: BackgroundFood insecurity (FI) is the situation where people do not have, at all times, access to sufficient, safe and nutritious food that meets their dietary needs for an active and healthy life. The objectives of this study were to estimate the prevalence of FI in the Paris area by using, for the first time in France, a specific FI questionnaire and to identify the characteristics of food-insecure households, taking into account a potential neighbourhood effect.MethodsThis study is based on data from the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
69
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 44 publications
9
69
2
2
Order By: Relevance
“…Consistent with previous studies carried out in the USA, Canada, England, Finland and one French region (9,13,31,33,34,43) , the present study showed that individuals reporting household FI were younger, more frequently women, single parents with children, non-home owners and had lower income than those living in foodsecure households. The greater vulnerability of women could result from the dynamic nature of experiencing FI within the household: parents, particularly women, tend to deprive themselves to protect their children against hunger (6) .…”
Section: Prevalence Of Food Insecuritysupporting
confidence: 92%
See 4 more Smart Citations
“…Consistent with previous studies carried out in the USA, Canada, England, Finland and one French region (9,13,31,33,34,43) , the present study showed that individuals reporting household FI were younger, more frequently women, single parents with children, non-home owners and had lower income than those living in foodsecure households. The greater vulnerability of women could result from the dynamic nature of experiencing FI within the household: parents, particularly women, tend to deprive themselves to protect their children against hunger (6) .…”
Section: Prevalence Of Food Insecuritysupporting
confidence: 92%
“…2). (56) , and is higher than that observed in both Canada in 2007-2008 (7·7 %) (57) and the Paris metropolitan area, which is the wealthiest region in France, in 2010 (6·3 %) (13,58) . Beyond methodological differences between studies (in particular regarding FI assessment), variation in FI prevalence between countries may be due to differences in the state of national economies, socio-economic characteristics of the population (e.g.…”
Section: Prevalence Of Food Insecuritymentioning
confidence: 65%
See 3 more Smart Citations